Sistem Informasi Penerimaan Siswa Sekolah Baru PadaPAUD Tunas Harapan II Berbasis Web - kanafi, Kanafi; YUSNANTO, TRI; Wahyudiono, Sugeng; Machmudi, Moch Ali (STMIK BINA PATRIA, 2025)
Tunas Harapan II Early Childhood School information system as a means of web new student admission. The purpose of this study is to design and build a Tunas Harapan II Early Childhood School information system as a means of web new student admission so that it can determine the impact obtained by Tunas Harapan II Early Childhood School after applying school new student admission information system. The research methodology used is the development method with Waterfall model. The stages of Waterfall method are Communication, Planning, Modeling, Construction, Deployment. The design in this study using DFD. DFD (Data Flow Diagram) is a graphic technique that describes the design of information that is applied when data moves from input to output, the depiction of which is arranged in a collection of interconnectied components. The results of this study are successful in creating a web-based promotional information system with a web-based registration feature at the Tunas Harapan II Early Childhood School to facilitate work in the sales process.Keywords : New Student Admission Information System, DFD, Waterfall, Web, Tunas Harapan II Early Childhood School.